Peptide-Based Biomaterials for Combatting Infections and Improving Drug Delivery - Lucia Lombardi; Jiaxu Li; Daryl R. Williams (MDPI AG, 2024)
This review explores the potential of peptide-based biomaterials to enhance biomedical applications through self-assembly, biological responsiveness, and selective targeting. Peptides are presented as versatile agents for antimicrobial activity and drug delivery, with recent approaches incorporating antimicrobial peptides into self-assembling systems to improve effectiveness and reduce resistance. The review also covers peptide-based nanocarriers for cancer drug delivery, highlighting their improved stability, targeted delivery, and reduced side effects. The focus of this work is on the bioactive properties of peptides, particularly in infection control and drug delivery, rather than on their structural design or material characteristics. Additionally, it examines the role of peptidomimetics in broadening biomaterial applications and enhancing resistance to enzymatic degradation. Finally, the review discusses the commercial prospects and challenges of translating peptide biomaterials into clinical applications.